Educational planning for situations of instability: standardization and advocacy in humanitarian aid practice - Karpinska, Z (2012)
This thesis examines the role and relationship of standardization and advocacy in humanitarian aid planning processes within the emergent field of education and instability. Standardization refers to the aid industry’s increasing emphasis on establishing ‘universal’ principles and normative frameworks. Advocacy refers to transnational-policy-network activities that move forward the global standardization agenda. The study focuses on the purposes and practices of knowledge creation by an education-and-instability ‘epistemic community’: the Inter-Agency Network for Education in Emergencies (INEE). Drawing on global-level interviews with key figures, participant observations, and documentary analysis, the research explores how this epistemic community promotes its core tenets: that education is an inherent human right and that educational provision should be a frontline humanitarian response on par with food distribution and shelter construction. The thesis analyzes the consensus-making process that resulted in the publication of the 2004 INEE Minimum Standards handbook, the then-epitome of the epistemic community’s knowledge. Next, the thesis examines the local application and adaptation of such global standardization processes in post-conflict Uganda. The case study presents the relationships among international and local ‘development partner’ institutions concerned with educational planning as a complex and contradictory story of power dynamics and knowledge circulation. These ‘partnerships’ are characterized by a shared quest for adherence to the knowledge encapsulated within standardized global frameworks and their normative principles. For Ugandan institutions, fluency in this discourse is a powerful tool to appropriate for their own ends. For international institutions, the knowledge is at once a technical resource and a means to bring ever more stakeholders into the wider epistemic community concerned with humanitarian aid. I argue that, through judicious use of standardization and advocacy mechanisms, INEE seeks to legitimize the education sector’s existence within the humanitarian aid industry and expand support for (or ‘conversion’ to) the education-and-instability epistemic community’s core beliefs.